Shipping in Inuit Nunangat Governance Challenges and Approaches in Canadian Arctic Waters - Bartenstein, Kristin (Publications on Ocean Development Series, 2023)
This timely overview of insights into the governance issues surrounding shipping in Inuit Nunangat, the homeland of Inuit in Arctic Canada, will inform and assist decision-makers, stakeholders and rights holders developing future law and policy in Canada and abroad